Gender-Specific Hierarchy in Nuage Localization of PIWI-Interacting RNA Factors in Drosophila - Siomi, Mikiko C.; Nagao, Akihiro; Sato, Kaoru; Nishida, Kazumichi M.; Siomi, Haruhiko (Frontiers in Genetics, 2011)
PIWI-interacting RNAs (piRNAs) are germline-specific small non-coding RNAs that form piRNA-induced silencing complexes (piRISCs) by associating with PIWI proteins, a subclade of the Argonaute proteins predominantly expressed in the germline. piRISCs protect the integrity of the germline genome from invasive transposable DNA elements by silencing them. Multiple piRNA biogenesis factors have been identified in Drosophila. The majority of piRNA factors are localized in the nuage, electron-dense non-membranous cytoplasmic structures located in the perinuclear regions of germ cells. Thus, piRNA biogenesis is thought to occur in the nuage in germ cells. Immunofluorescence analyses of ovaries from piRNA factor mutants have revealed a localization hierarchy of piRNA factors in female nuage. However, whether this hierarchy is female-specific or can also be applied in male gonads remains undetermined. Here, we show by immunostaining of both ovaries and testes from piRNA factor mutants that the molecular hierarchy of piRNA factors shows gender-specificity, especially for Krimper (Krimp), a Tudor-domain containing protein of unknown function(s): Krimp is dispensable for PIWI protein Aubergine (Aub) nuage localization in ovaries but Krimp and Aub require each other for their proper nuage localization in testes. This suggests that the functional requirement of Krimp in piRNA biogenesis may be different in male and female gonads.